Influence of tragacanth resin on the thermal and mechanical properties of fly ash-cement composites - Bicer, Ayse (Taylor & Francis Ltd, 2019)
This study was aimed to search the possibility of usage of the thermal power plants fly ashes, cement and tragacanth composites in concrete or plaster by investigating their thermal insulation characteristics. The fly ash used in the experiments is supplied from Afsin Elbistan Thermal Power Station. Portland cement (KPC 325) with resin is used as binding and 24 specimens are prepared depending on the percentage of fly ash and tragacanth. In all fly ash, tragacanth and binding mixture, the weight percentages of fly ash are taken as 0, 10, 20, 30, 40 and 50%. The amount of the resin in the mixture is 0.5, 1 and 1.5% of the weight of the total cement and fly ash. 24 samples were prepared and tested to find out the effects of resin on thermal and mechanical properties of fly ash and cement composites. Whereas fly ash percentage increased from 0% to 50%, i) thermal conductivity and compressive strength decreased 19.37-28.62% and 7.66-16.55% respectively as the porosities of the samples increased 18.91-28.62% with the effect of artificial pores generated by 1.5% resin other than the pores generated by fly ash. ii) the new produced samples can be used as partition walls, floorings, ceiling concretes, briquettes or bricks and plaster.
Keywords: Fly ash; tragacanth; cement; light concrete; insulation plaster